(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The improvement of the education system in Kyrgyzstan is closely related to the improvement of the qualifications of teachers. In particular, a teacher’s music plays an important role in ensuring the aesthetic education of students. In this article, the main requirements for the future music teacher, his professional training and competence are analyzed. The main requirements for future music teachers are considered in this article. A music teacher must have pedagogical skills, musical knowledge, creative abilities and innovative teaching methods. Also, he must improve his psychological and communicative skills and effectively conduct the educational process using modern technologies. The article analyzes the professional training of teachers, the method of working with students, the role of cultural education. Increasing the competence of music teachers is an important factor in improving the quality of general education.